1965
DOI: 10.1111/j.1467-8306.1965.tb00531.x
|View full text |Cite
|
Sign up to set email alerts
|

SOME GENERALIZATIONS CONCERNING PRIMATE CITIES1

Abstract: Six hypotheses are formulated and tested on the conditions under which primate cities occur. Using worldwide data, it was found that high urban primacy occurs most frequently in countries with small areal extent of dense population, low per capita income, export-oriented and agricultural economies, a colonial history, and rapid rates of population growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

1989
1989
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(20 citation statements)
references
References 7 publications
0
19
0
1
Order By: Relevance
“…Mehta (1964) found that primacy was a function of the small area and population size of countries. Linsky (1965) proposed that high urban primacy is most often associated with countries of small extent but high density, low per capita income, export‐oriented and agricultural economies, a colonial history, and rapid rates of population growth. Ades and Glaeser (1995) correlated urban primacy with political instability and high levels of centralized political power.…”
Section: Urban Primacymentioning
confidence: 99%
“…Mehta (1964) found that primacy was a function of the small area and population size of countries. Linsky (1965) proposed that high urban primacy is most often associated with countries of small extent but high density, low per capita income, export‐oriented and agricultural economies, a colonial history, and rapid rates of population growth. Ades and Glaeser (1995) correlated urban primacy with political instability and high levels of centralized political power.…”
Section: Urban Primacymentioning
confidence: 99%
“…Rank-size distributions featuring such a distinct "primate city" (following Jefferson 1939;Morse 1962;Mehta 1964;Linsky 1965), associated with smaller settlements that adhere roughly to the rank-size rule, may be attributed to conditions of low system closure and high interdependence between communities (Vapnarsky 1968). Indeed, Uruk stood at the center of a far-flung network of economic and political interaction with neighboring regions (Algaze 1989).…”
Section: Rank-size Perspectives On Early Urbanismmentioning
confidence: 99%
“…Given the large geographical size of India and the lop-sided regional economic development [29], this is plausible. Linsky [30] has pointed out that primacy will be more prominent in countries with small territorial extents, but it is noteworthy that India has a large territorial extent. However, the states in India are of the size of many European countries and, as such, the polarized development within the individual states has created a primacy within these states.…”
Section: Rank-size Rulementioning
confidence: 99%